Mapping of Soil pH and NPK Nutrients on Peat Agricultural Land in Kalampangan Village, Palangka Raya City - Agustiani, Reni; Kurniawati, Neny; Arifin, samsul; Andanu, Odi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2025)
Kalampangan Village is one of the villages in Sebangau District, Palangka Raya City, Central Kalimantan Province. Kalampangan Village has an area of 5000Ha with a population of 4000 people. The main livelihood of the population is farming. Farmers convert peatlands into agricultural land to grow food crops. The main challenge of farming on peatlands is the high acidity value of peat soil which causes low soil nutrient content and decreases soil fertility. Therefore, this study aims to map the distribution of nutrient content and acidity of peat agricultural soil in Kelampangan Village. Data measurement in agricultural land was carried out using the Soil Sensor 5 Pin Probe RS485 NPKPHCTH-HMI043 by inserting the sensor feet into the ground and the results will be displayed on the HMI touch screen. While the coordinate points of data collection use the Global Positioning System. The data measurements obtained were analyzed using the Geographic Information System (GIS) application to produce a thematic map of the distribution of soil pH and NPK nutrients. The results show that peat agricultural land in Kalampangan tends to be slightly acidic (pH 4.48-6.64) with majority low N (0-1.24 mg/kg), P (0-18.44 mg/kg), and K (0-14.61 mg/kg) content. The resulting thematic map can be used as a reference for farmers to process peat agricultural land to be more productive, for local governments in formulating agricultural policies, and contribute to the development of science in the field of soil science.